A methodology to empower citizens towards a low-carbon economy. The potential of schools and sustainability indicators. (15th April 2021) - Lizana, Jesus; Manteigas, Vítor; Chacartegui, Ricardo; Lage, Joana; Becerra, Jose A.; Blondeau, Patrice; Rato, Ricardo; Silva, Filipe; Gamarra, Ana R.; Herrera, Israel; Gomes, Margarida; Fernandez, Amaia; et al.
Abstract: Environmental empowering to control resource consumption and environmental impacts is critical to engage citizens to adopt more sustainable habits. This study demonstrates the potential benefits of innovative approaches based on sustainability indicators towards a low-carbon economy. A methodology to measure and promote sustainability in schools has been proposed and evaluated, aiming at showing the environmental performance and informing of potential environmental savings. The methodology, titled ClimACT, has two main purposes: measuring the environmental performance of schools through a school sustainability index based on measurable indicators in the areas of transport, procurement, green spaces, indoor air quality, energy, water and waste; and encouraging students, teachers and families towards an energy-efficient and low-carbon pathway through a structural procedure based on roles, activities and progress evaluation. The approach, applied to 39 pilot schools from Portugal, Spain, France and Gibraltar, achieved promising and encouraging results. All schools deployed the methodology successfully, achieving measurable environmental benefits in 95% of cases, with an average improvement of 10% in the global performance of schools after one year. Moreover, the 5112 surveys applied to school communities, before and after the methodology implementation, highlighted how the sustainable indicators had a significant influence on the daily lives of families, leading to improvements of their behaviour, with an average increase of 20% in indicators regarding good practices in transport, energy, water, waste and citizenship. The environmental empowering through measurable indicators is a step forward a low-carbon economy. This methodology is open and adaptable to all sectors and requirements. Graphical abstract: Image 1 Highlights: Empowering school communities towards a low-carbon economy. The paper proposes a methodology to measure and promote sustainability. The methodology was evaluated in 39 pilot schools from 4 European countries. After one year, 95% of schools achieve measurable environmental benefits. Sustainability indicators are proposed as key elements towards sustainability.